Kant and the Duty to Stay in the State of Nature - Slenzok, Norbert; Trzcionka, Patryk (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The paper tackles the question as to whether Kant has successfully substantiated his claim that there exists a moral and juridical duty to leave the state of nature. Our thesis is that he has not. In the first step, it is demonstrated that Kant’s concept of provisional ownership is a logical impossibility. Thus, property rights themselves cannot generate the duty to submit to the state. The only way to argue for the duty to exit statelessness that the Kantian is left with is therefore to conceive of that duty as implied directly by the right to freedom. Yet, one may plausibly argue that at the conceptual level, public law runs afoul of Kant’s notion of freedom to a greater degree than private law does. Therefore, in virtue of the innate right to freedom, a prima facie duty arises to stay in the state of nature.